Transitional justice against the state: lessons from Spanish civil society-led forensic exhumations - Rubin, Jonah S. (International journal of transitional justice, 2014)
Inspired by forensic exhumations that have occurred in the context of transitional justice processes elsewhere, Spanish civil society associations since 2000 have helped relatives of the disappeared locate, exhume and honor those who were killed in the Spanish Civil War and the ensuing Francisco Franco dictatorship. In the process, they have creatively adopted, applied and reinterpreted practices originally developed for state-led democratic transitions to civil society initiatives. In this article, I explore the ways transitional justice concepts take on a social life beyond their juridical applications. In so doing, I take these exhumations as an opportunity to examine some of the tensions between the bureaucratic state-led models of transitional justice that inspired Spanish activists and the civil society reinterpretations that mark forensic practice in contemporary Spain. The practice of Spanish organizations offers new avenues for understanding and ameliorating the tense relationship between the bureaucratic and legal needs of forensic exhumations and the desires and expectations of victims.2